TET proteins regulate Drosha expression and impact microRNAs in iNKT cells - Gioulbasani, Marianthi; Äijö, Tarmo; Valenzuela, Jair E.; Bettes, Julia Buquera; Tsagaratou, Ageliki (Frontiers in Immunology, 2024)
DNA demethylases TET2 and TET3 play a fundamental role in thymic invariant natural killer T (iNKT) cell differentiation by mediating DNA demethylation of genes encoding for lineage specifying factors. Paradoxically, differential gene expression analysis revealed that significant number of genes were upregulated upon TET2 and TET3 loss in iNKT cells. This unexpected finding could be potentially explained if loss of TET proteins was reducing the expression of proteins that suppress gene expression. In this study, we discover that TET2 and TET3 synergistically regulate Drosha expression, by generating 5hmC across the gene body and by impacting chromatin accessibility. As DROSHA is involved in microRNA biogenesis, we proceed to investigate the impact of TET2/3 loss on microRNAs in iNKT cells.We report that among the downregulated microRNAs are members of the Let-7 family that downregulate in vivo the expression of the iNKT cell lineage specifying factor PLZF. Our data link TET proteins with microRNA expression and reveal an additional layer of TET mediated regulation of gene expression.